INDUKSI MUTASI PADA TANAMAN PEDADA (Sonneratia caseolaris)MELALUI IRADIASI SINAR GAMMA - Sitanggang, Kamsia Dorliana (Universitas Islam Balitar, 2025)
Pedada is a plant has not been explore by many people. Pedada fruit can be found in Indonesian mangrove forest. The fresh fruit of Pedada can be eat and also made into processed drinks such as syrup. One technique that can be used to improve the properties of Pedada is gamma ray irradiation. This research aim to observe the growth of pedada plant resulting from gamma ray irradiation with doses of 0,20,40,60,80 and 100 Gray. This experiment used non-factorial randomized block design with 1 treatment is gamma ray irradiation. Each of dose gamma ray irradiation was repeated 3 times, and each replication consisted of 3 plants so there there were 54 plants. The results of this study showed that the highest death (30%) rate was doses of 20 and 30 Gray. For The height parameter, we can seen that control plantd is significally different from 20,40,60 and 100 gray irradiation. The number of leaves also we can seen control is sifnifically different with 40 gray irradiation. The stem diameter parameter also significantly different between control and 70 and 100 gray. Phenotypic cahaterized of Pedada also changes by irradiation gamma ray with doses 20,40,60 80 and 100 gray.